2011
DOI: 10.1093/ndt/gfr150
|View full text |Cite
|
Sign up to set email alerts
|

MDR-1 gene polymorphisms in steroid-responsive versus steroid-resistant nephrotic syndrome in children

Abstract: Patients with NS carrying homozygous mutants of single nucleotide polymorphism (SNP) G2677T/A are prone to develop SRNS. The synergistic effect of mutant genotypes of SNPs G2677T/A and C3435T in different combinations increase the risk of developing steroid resistance in patients with NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 25 publications
6
47
0
Order By: Relevance
“…We also found that the SNP C3435T variations were high among patients on compare with healthy children. In this study, distribution of C3435T, CC, CT, and TT genotype frequency is close to that in the Asians such as Japanese, Chinese, and Indian population [26]. In this study, the genotypic distribution of CT, TT, and CC was relatively high on compare with controls were as are showed C3435T, CT, CC, and TT genotype (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…We also found that the SNP C3435T variations were high among patients on compare with healthy children. In this study, distribution of C3435T, CC, CT, and TT genotype frequency is close to that in the Asians such as Japanese, Chinese, and Indian population [26]. In this study, the genotypic distribution of CT, TT, and CC was relatively high on compare with controls were as are showed C3435T, CT, CC, and TT genotype (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…[1417,3135] All of the participants in these studies were children consisting of 928 patients with INS and 879 healthy controls; moreover, steroid resistance data were available for 724 patients comprising 488 patients with SS and 236 patients with SR, which were compared. The subjects in 4 studies were Asian [16,17,34,35] and those from the other 5 were Caucasian. [14,15,3133] Seven studies reported genotype frequencies between patients with INS and healthy controls, [1416,31,32,34,35] and 7 studies showed the genotype data of SS and SR groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies yielded inconsistent results. Youssef et al [14] reported that the T allele and TT genotype of rs1045642, and the T allele and GT, TT, and TT + AA genotypes of rs2032582 were significantly increased in patients with INS, but no significant evidence of association was found with any of these 3 SNPs in the cohort tested by Cizmarikova et al [15] Jafar et al [16] showed that the frequencies of homozygous mutant TT/AA genotypes of rs2032582 were significantly increased in affected children with steroid resistance, whereas Chiou et al [17] observed a trend with the T allele of rs1128503 in their cohort.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies reported higher expression levels in 2677TT/A subjects [26], others showed no differences between genotypes [27]. In our previous work, we had observed that homozygous mutant of SNP G2677T/A is prone to develop steroid-resistant nephrotic syndrome [24]. Another mechanism that may be responsible for persistent expression of P-gp could be due epigenetic influence; DNA methylation, histone acetylation, and micro-RNA activity.…”
Section: Discussionmentioning
confidence: 85%